Exploration of Interfacial Porphine Coupling Schemes and Hybrid Systems by Bond‐Resolved Scanning Probe Microscopy. Issue 49 (15th November 2018) - Bischoff, Felix; He, Yuanqin; Riss, Alexander; Seufert, Knud; Auwärter, Willi; Barth, Johannes V.
Abstract: The templated synthesis of porphyrin‐based oligomers and heterosystems is of considerable interest for materials with tunable electronic gaps, photovoltaics, or sensing device elements. In this work, temperature‐induced dehydrogenative coupling between unsubstituted free‐base porphine units and their attachment to graphene nanoribbons on a well‐defined Ag(111) support are scrutinized by bond‐resolved scanning probe microscopy techniques. The detailed inspection of covalently fused porphine dimers obtained by in vacuo on‐surface synthesis clearly reveals atomistic details of coupling motifs, whereby also putative reaction intermediates are identified. Moreover, the covalent attachment of porphines at preferred locations of atomically precise armchair‐type graphene nanoribbons is demonstrated. Abstract : Interconnecting porphines and graphene nanoribbons : Porphine homocoupling and covalent attachment of porphines to graphene nanoribbons under atomically well‐defined on‐surface conditions was investigated by bond‐resolved scanning tunneling and atomic force microscopy. The thermally induced reactions on Ag(111) afford distinct coupling motifs, the relative abundance of which is associated with stepwise reaction mechanisms.